Influence of porosity on water vapor permeability behavior of warp knitted polyester spacer fabrics. (March 2016) - Rajan, T Palani; Souza, Louis D; Ramakrishnan, G; Kandhavadivu, P; Vigneswaran, C
Linear density of filament, fabric structure, and number of loops per unit area are the major factors which influence the porosity of warp knitted spacer fabrics. The characteristics of air and water permeability of textile fabrics are chiefly influenced by the porosity of the fabric. An attempt has been made to analyze the water vapor permeability of warp knitted polyester spacer fabric. Spacer fabric face and back surface layers are constructed by polyester multifilament and the middle layer is connected to the two surface layers by polyester monofilament. The behavior of porosity and water vapor permeability were analyzed with respect to the linear density of polyester. The experimental result indicates that the water vapor permeability is highly influenced by porosity of a fabric. The statistical analysis proves the degree of correlation between polyester linear density of spacer fabric layers and their responses. The face and middle layers of fabric are highly significant with the porosity and water vapor permeability. Box–Behnken model was adopted for optimization and a better R 2 value of 96.5% is achieved in porosity and the water vapor permeability is 92%.